Microstructural Characteristic of Co-Cr-Mo Powder Alloy Coating on Stainless Steel by Plasma Transferred Arc Weld Surfacing - Somunkiran, Ilyas; Kurt, Bulent; Buytoz, Soner; Orhan, Nuri (Carl Hanser Verlag, 2010)
In this study, Co-Cr-Mo powder was coated on the surface of AISI 304 stainless steel by the plasma transfer arc (PTA) process at 80, 90 and 100 A current values and argon gas was used for both plasma and protective. Deposition layers were examined with optical microscopy, SEM, EDX, XRD analysis and microhardness test. The thickness of the coating increased with current density. No cracks or pores were detected in the interface and coating layer. Higher current levels resulted in higher dilution levels and also in melting/burning of the substrate.
Mikrostruktureigenschaften einer Beschichtung aus einer Legierung aus Co-Cr-Mo-Pulver auf rostfreiem Stahl mittels Plasmaauftragsschweißen mit übertragenem Lichtbogen
Keywords: Stellite Hardfacing Alloys; Mechanical Characteristics; Composite Coatings; Wear-Resistance; Ni-Cr; Fe; Molybdenum; Behavior